A model for size and age changes in the pharmacokinetics of paracetamol in neonates, infants and children - Anderson, Brian J (Blackwell Science Inc, 2000)
AIMS: The aims of this study were to describe paracetamol pharmacokinetics in neonates and infants. METHODS: Infants in their first 3 months of life (n = 30) were randomised to sequentially receive one of three paracetamol formulations (dose 30–40 mg kg(−1)) over a 2 day period. The formulations were (a) elixir, (b) glycogelatin capsule suppository and (c) triglyceride base suppository. Approximately six blood samples were taken after each dose over the subsequent 10–16 h. Data were analysed using a nonlinear mixed effect model. These neonatal and infant data were then included with data from four published studies of paracetamol pharmacokinetics (n = 221) and age-related pharmacokinetic changes investigated. RESULTS: Population pharmacokinetic parameter estimates and their coefficients of variation (CV%) for a one compartment model with first order input, lag time and first order elimination were volume of distribution 69.9 (18%) l and clearance 13.0 (41%) l h(−1) (standardized to a 70 kg person). The volume of distribution decreased exponentially with a half-life of 1.9 days from 120 l 70 kg(−1) at birth to 69.9 l 70 kg(−1) by 14 days. Clearance increased from birth (4.9 l h(−1) 70 kg(−1)) with a half-life of 3.25 months to reach 12.4 l h(−1) 70 kg(−1) by 12 months. The absorption half-life (t(abs)) for the oral preparation was 0.13 (154%) h with a lag time (t(lag)) of 0.39 h (31%). Absorption parameters for the triglyceride base and capsule suppositories were t(abs) 1.34 (90%) h, t(lag) 0.14 h (31%) and t(abs) 0.65 (63%) h, t(lag) 0.54 h (31%), respectively. The t(abs) for elixir and capsule suppository in children under 3 months were 3.68 and 1.51 times greater than children over 3 months. The relative bioavailability of rectal formulations compared with elixir were 0.67 (30%) and 0.61 (23%) for the triglyceride base and capsule suppositories, respectively. CONCLUSIONS: Total body clearance of paracetamol at birth is 62% and volume of distribution 174% that of older children. A target concentration above 10 mg l(−1) in approximately 50% subjects can be achieved by a dose from 45 mg kg(−1) day(−1) at birth and up to 90 mg kg(−1) day(−1) in 5-year-old children. A reduced dose of 75 mg kg(−1) day(−1) in an 8-year-old child is sufficient because clearance is a nonlinear function of weight.